Застосування методів і інструментів маркетингу для розвитку внутрішнього туризму в умовах пандемії COVID-19 - Ілляшенко, Сергій Миколайович; Шипуліна, Юлія Сергіївна; Ілляшенко, Наталія Сергіївна (Одеський національний політехнічний університет, 2021)
Показано, що згортання надходжень від міжнародного туризму в умовах пандемії COVID-19 може бути компенсовано розвитком внутрішнього туризму. Розвиток внутрішнього туризму також дозволить підготуватися до відновлення ринку міжнародних туристичних послуг після спаду пандемії. Уточнено основні складові туристичного потенціалу регіонів України з погляду їх придатності для розвитку внутрішнього і міжнародного туризму. Удосконалено підхід до оцінки доцільності розвитку конкретних видів внутрішнього туризму в регіонах країни, виходячи з їх туристичного потенціалу, стану туристичної інфраструктури, наявних ринкових можливостей і загроз з урахуванням впливу пандемії COVID-19. Уточнена структура туристичного іміджу регіону. Окреслено коло комунікаційних інструментів формування туристичного іміджу і бренду регіону. Отримані результати у комплексі формують підхід до розроблення на засадах маркетингу туристичного іміджу та бренду регіону для розвитку внутрішнього туризму в період пандемії COVID-19, а в подальшій перспективі після завершення карантинних обмежень - для виходу на міжнародний ринок туристичних послуг.

The global pandemic COVID-19 has negatively affected the entire world economy. The tourism sector has suffered greatly from it. More than a hundred countries have imposed restrictions on entry into their territories, which has reduced their revenues from the tourism industry. This has led to significant losses, as the share of tourism in the economy of foreign countries is about 10% (international average). One of the most effective measures to correct the negative trends in the field of tourism is the development of domestic tourism, which should compensate for the losses caused by reducing the flow of foreign tourists. In countries with developed tourism, their share is up to 90%. Ukraine's tourism industry is less dependent on foreign tourists, accounting for about a third of the total. However, domestic tourism can not only provide rapid results that will offset the current losses, but will also prepare for the development of international tourism after the recession of the COVID-19 pandemic. In view of the above, there is a problem of finding ways to develop domestic tourism in Ukraine with the prospect of strengthening the position of the domestic tourism industry in the international market of tourist services. The purpose of the article is development of an approach to the formation on the basis of marketing of the tourist image and brand of the region for the development of domestic tourism in the period and after the pandemic COVID-19 with the prospect of further entry into the international market of tourist services. Based on statistics, it is shown that the development of domestic tourism can not only compensate for the curtailment of revenues from international tourism in the context of the COVID-19 pandemic, but also prepare for the recovery of the international tourism services market after the recession of the COVID-19 pandemic. The main components of the tourist potential of the regions of Ukraine are specified. The approach to assessing the feasibility of developing certain types of domestic tourism in specific regions of the country has been improved, based on their tourism potential, the state of tourism infrastructure, existing market opportunities and threats, taking into account the impact of the COVID-19 pandemic. Its practical approbation is executed. The structure of the tourist image of the region has been clarified. The range of communication tools for the formation of the tourist image and brand of the region is outlined. The obtained results form an approach to the development on the basis of marketing the tourist image and brand of the region for the development of domestic tourism during the pandemic COVID-19, and in the future after the end of quarantine restrictions - to enter the international market of tourist services.
Application of marketing methods and tools for the development of domestic tourism in a pandemic COVID-19
Keywords: маркетинг туризму; туристичний імідж; туристичний бренд; регіональний туризм; tourism marketing; domestic tourism; tourist image; tourist brand; regional tourism